GreenScheduler: Coordinated Two-Tier Energy Optimization for Disaggregated LLM Serving (Comprehensive Journal of Science, 2026)
Large Language Model (LLM) inference has become a dominant consumer of en- ergy in modern AI data centers, often accounting for over 90% of total operational power [1].Recent architectural shifts toward prefill/decode disaggregation have improved perfor- mance but created complex energy optimization challenges. This paper introduces Green- Scheduler, a novel two-tier framework designed to jointly optimize GPU placement and Dynamic Voltage and Frequency Scaling (DVFS) in disaggregated environments. Tier 1 performs coarse-grained (minute-scale) phase-aware provisioning using predictive work- load modeling, while Tier 2 executes fine-grained (millisecond-scale) frequency control. For the compute-bound prefill stage, GreenScheduler employs Model Predictive Control (MPC) to manage queue dynamics; for the memory-bound decode stage, it utilizes a lightweight slack-aware adaptation mechanism. Evaluations using production Azure traces[2] on an H100 cluster demonstrate that GreenScheduler achieves significant energy reduc- tion in both decode and prefill pools compared to performance-optimized baselines like DistServe [3], while strictly maintaining Time to First Token (TTFT) and Time Per Output Token (TPOT) Service-Level Objectives (SLOs).